Pengaruh Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Kantor Kelurahan di Kecamatan Pasar Kliwon Kota Surakarta - Utama, Dimas Anggara Satria, Drs. Farid Wajdi, MM, Ph (2016)
The aim of this research is to recognize several factors that influence the employess' performance at the Village Office in Pasar Kliwon District of Surakarta City, be reviewed based on the factors that influence it that are the stryle of leadership and job motivation. Examination that has been done in this research uses the test of research intrument that are validity test and realibility test, hipothesis test that are double linear regression test, T test, F test and coefficient determination test or R2. Data on this research is primary data that has been obtained by spread the questionare to respondents (Village Office in Pasar Kliwon District of Surakarta City), samples that be taken are 50 employees with 35 samples of valid questionare. Based on the research result, it can be shown that the style of leadership variable is a variable that has dominant influence to the employees' performance at the Village Office in Pasar Kliwon Distroct of Surakarta City. Proved in T test, variable of leadership style and job motivation have a significant influence to employees' performance, because the result of T test statistic (thitung) bigger than the value of ttable (3.243 > 2.035) and (2.241 > 2.035). Result in F test shows the existance simultant and significant influence among the leadership style variable and job motivation to the employess' performance, bacause the result of F test statistic (Fhitung) bigger than the value of Ftable (12.532 > 4.17) with probability that is smaller than 0.05 (0.000956 < 0.05). Result obtain determination of coefficient number or R2 as big as 0.439, this thing means 43.9% of the employees' performance fluctuation caused by the change of leadership style variable and job motivation. Whereas the 56.1% caused by the other factors that is not be analyzed in the model that are used on the research.